Manhaj Muqtarah Fi Ta’lim Al Lughah Al Arabiyyah Bi Istikhdami Al Kalimat Al Indunisiyyah Dzatu Aslin Arabi Fi Al Mu’jam Al Munawwir - Nadiyah Husna Millati; Rizal Firdaus (Ukazh: Journal of Arabic Studies, 2020)
يهدف هذا البحث إلى معرفة الطريقة المقترحة في تدريس مفردات اللغة العربية لها معنى في اللغة الإندونيسية على أساس المعجم المنور من حرف W إلى Z ، من خلال تقديم الطريقة الصحيحة في عملية التعليم والتعلم بحيث يمكن أن تساعد المعلمين والطلاب، ثم تشرح بعد ذلك كيفية التطبيق في استخدام المنهج لتسهيل فهم الطلاب الإندونيسيين المبتدئيين. إن هذه الدراسة تسلك على منهج الوصفي التحليلي وهي طريقة مايلز وهوبرمان، وذلك بتتبع المفردات الموجودة في المعجم المنور من حرف W إلى Z ، وجمعها، وتصنيفها، وعرضها والاستنتاج. وأيضا من الطرق المقترحة في تعليمها كالناص الحواري (المحادثة)، والناص القرائي، وتقسيم الجملة وكذا الألعاب اللغوية من خلال التمارين التي عززت المهارات الأربع، وهي مهارات الكتابة، القراءة، الكلام والاستماع. This research aims to find out the suggested method in teaching Indonesian Arabic vocabulary based on the “Al-Munawwir Dictionary” of the letter W-Z, by presenting the right method in the teaching and learning procesess, as it can help students and muslim, then explain how to apply it in the use of the curriculum to facilitate understanding for beginner-level Indonesian students. The research method used is a qualitative method using Miles and Huberman analysis techniques, namely research procedures with steps to trace Indonesian sentences from Arabic from the letter W-Z in “Dictionary of Al-Munawwirr”, data collection, data classification, data exposure, data conclusions (research result). This study also formulated several affective ways of learning these sentences, by presenting various methods such as the hiwar method (conversation), nas qiroi (reading text), sentence division and various language games by accompanying various exercises that fostered the four skills, namely reading skills writing, speaking and listening.